2021
DOI: 10.1002/essoar.10509394.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling Forest Complexity: Resource Use Efficiency, Disturbance, and the Structure-Function Relationship

Abstract: Structurally complex forests optimize light and water resources to assimilate carbon more effectively, leading to higher productivity. Information obtained from Light Detection and Ranging (LiDAR)-derived structural complexity (SC) metrics across spatial scales serves as a powerful indicator of ecosystem-scale functions such as gross primary productivity (GPP). However, our understanding of mechanistic links between forest structure and function, and the impact of disturbance on the relationship, is limited. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The assumptions that go into such a data assimilation consequently generates a large source of uncertainty for upscaling. Recent work from CHEESEHEAD19 also highlights the legacy of a century of land management leaving behind a significant imprint on stand structure and linkages to carbon and water use efficiency (Murphy et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumptions that go into such a data assimilation consequently generates a large source of uncertainty for upscaling. Recent work from CHEESEHEAD19 also highlights the legacy of a century of land management leaving behind a significant imprint on stand structure and linkages to carbon and water use efficiency (Murphy et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation of CO 2 fluxes from a collection of sites in and around the Chequamegon‐Nicolet National Forest in the summers of 2002 and 2003 demonstrated that footprint‐weighted NEE, R eco , and GPP at the tall tower were within 11% of the combined fluxes from 13 surrounding towers (Desai, Noormets, et al., 2008). Forest structure and age distribution strongly impact these fluxes, reflecting the history of land management and canopy complexity on modulating regional carbon cycle responses in forests (Desai et al., 2005, 2007; Murphy et al., 2022). Wetlands and other aquatic landscapes (lakes, rivers, and ponds) form more than a quarter of the landscape and have been shown to have unique responses to hydrologic change (Buffam et al., 2011; Gorsky et al., 2021; Pugh et al., 2018; Turner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, from CHEESEHEAD19, Murphy et al. (2022) find canopy structural metrics do not linearly scale with spatial resolution, which influences how those metrics link to ecosystem functions through water‐use and light‐use efficiencies. Meanwhile, with a range of atmospheric profilers and surface radiation observations, Sedlar et al.…”
Section: A Scale For All Silosmentioning
confidence: 99%